1986
DOI: 10.3109/00498258609043524
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and excretion of enzyme-inducing doses of phenobarbital by rats with bile fistulas

Abstract: The metabolism of enzyme-inducing doses of 14C-phenobarbital injected i. p. into bile duct-cannulated rats has been studied using improved chromatographic separation and quantification techniques. In animals with bile fistulas most of the 14C-phenobarbital was excreted in bile as p-hydroxyphenobarbital conjugated with glucuronic acid. In urine the main substance found was phenobarbital, with significant amounts of p-hydroxyphenobarbital and varying amounts of its glucuronide conjugate. Animals without bile fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…An exhaustive mass spectral analysis of the microsomal extracts showed trace quantities of a hydroxylated metabolite. This finding is consistent with the observations made by previous investigators who found lack of in vitro metabolism of PB in microsomal systems and in cultured rat hepatocytes (Levin et al, 1986;Verite et al, 1996). However it has been shown in vivo that PB is metabolized in rats and humans with the formation of a hydroxylated metabolite that is subsequently conjugated with glucuronic acid (Levin et al, 1986;Whyte et al, 1977).…”
Section: Effect Of Phenobarbital and Phenytoin On Apap Glucuronidation By Expressed Forms Of Human Ugts And Human Liver Microsomessupporting
confidence: 92%
“…An exhaustive mass spectral analysis of the microsomal extracts showed trace quantities of a hydroxylated metabolite. This finding is consistent with the observations made by previous investigators who found lack of in vitro metabolism of PB in microsomal systems and in cultured rat hepatocytes (Levin et al, 1986;Verite et al, 1996). However it has been shown in vivo that PB is metabolized in rats and humans with the formation of a hydroxylated metabolite that is subsequently conjugated with glucuronic acid (Levin et al, 1986;Whyte et al, 1977).…”
Section: Effect Of Phenobarbital and Phenytoin On Apap Glucuronidation By Expressed Forms Of Human Ugts And Human Liver Microsomessupporting
confidence: 92%
“…Twenty-five percent of PB is cleared by renal excretion in unchanged form [87]. After administration, PB was detected in hepatic tissue and the portal vein, vena cava, and aorta [88], suggesting that the liver is the main organ for the metabolism of PB. The metabolites of PB include free PB and two inactive metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…PB, p-OHPB and p-OHPBG are the major species found in bile after a dose of PB (Levin et al, 1986). Among them, only p-OHPBG markedly inhibited Mrp2-mediated CDF uptake.…”
Section: Mechanisms Of Impaired Biliary Excretion Of Ag By Pb (52)mentioning
confidence: 99%
“…PB is metabolized in the liver by cytochrome P450 enzymes to p-hydroxyphenobarbital ( p-OHPB), which is metabolized further primarily to p-hydroxyphenobarbital glucuronide ( p-OHPBG). In rats with bile fistula, approximately 20 to 30% of the PB dose recovered in bile was the parent compound, and 50 to 60% was free or conjugated p-OHPB (mainly p-OHPBG) (Levin et al, 1986). The transport mechanisms for biliary excretion of PB, p-OHPB, and p-OHPBG have not been clarified.…”
mentioning
confidence: 99%